FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN TRADISI TOHO WAE PADA REMAJA PUTRI DI DESA WAELO KECAMATAN FENA FAFAN KABUPATEN BURU SELATAN - Petriana Mahmud; Mike Yuliana Liligoly (Pasapua Health Journal, 2021)
Introduction: The implementation of female circumcision on Buru Island is known as Toho Wae. Toho Wae literally means getting into the water or getting circumcised or soaking in the water. Purpose: to identify factors related to the implementation of the Toho Wae Tradition for young women in Waelo Village, Fena Fafan District, South Buru Regency. Method: Quantitative study, with an analytic survey design using a cross sectional study approach. The population and sample in the study amounted to 40 people. Results: There is a relationship between knowledge and the implementation of the Toho Wae Tradition for young women in Waelo Village, Fena Fafan District, South Buru Regency with a value of ρ = 0.022 <0.05. There is an attitude relationship with the implementation of the Toho Wae Tradition for young women in Waelo Village, District Fena Fafan, South Buru Regency with a value of 0.036 <0.05. There is a relationship between education and the implementation of the Toho Wae Tradition for young women in Waelo Village, Fena Fafan District, South Buru Regency in 2020 with a value of 0.036 <0.05 Conclusion: There is a relationship between knowledge, attitudes, and education with the implementation of the Toho Wae Tradition for young women in Waelo Village, Fena Fafan District, South Buru Regency